ANALISIS ASAS KEMANFAATAN HUKUM TERHADAP DISPARITAS PUTUSAN HAKIM DALAM TINDAK PIDANA PENCEMARAN NAMA BAIK DI MEDIA SOSIAL - KATRIN WULANDARI MO’O; FENTY U. PULUHULAWA; JUFRYANTO PULUHULAWA (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to determine and analyze the principle of legal expediency regarding disparities in judges’ verdicts regarding criminal offence of defamation on social media. The research was classified as qualitative-normative research with statute and case approaches. The research findings elucidated that expediency can be defined as a way to provide maximum good and reduce harm to a minimum so that the results can be enjoyed by as many people must not be achieved at the expense of individual freedom and rights. Thus, judges, as the spearhead of justice enforcement, should have the same perception regarding applying the principle of freedom of judge in imposing criminal sentences, which must be in accordance with the aims and functions of the law, namely, justice, certainty and expediency